2012
DOI: 10.1016/j.pain.2012.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone treatment for sustained pain reduction and improvement in quality of life in severe fibromyalgia

Abstract: Functional defects in growth hormone (GH) secretion and its efficacy as a complementary treatment have been suggested for fibromyalgia. This study investigated the efficacy and safety of low-dose GH as an add-on therapy in patients with both severe FM and low insulin-like growth factor 1 levels. A total of 120 patients were enrolled in a multicenter, placebo-controlled study for 18 months. They were randomly assigned to receive either 0.006 mg/kg/day of GH subcutaneously (group A, n=60) or placebo (group B, n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 21 publications
3
26
0
3
Order By: Relevance
“…Exploration of trace (biomarker) associated with the pathophysiology is ongoing using various methodologies. For example, deficiencies in the growth hormone insulin-like growth factor cascade are associated with chronic pain at least in subgroup of patients with fibromyalgia [15]. A recent study using rectal biopsy samples has suggested that densities of rectal peptide YY and somatostatin cells are significantly altered in IBS patients [16].…”
Section: Editorialmentioning
confidence: 99%
“…Exploration of trace (biomarker) associated with the pathophysiology is ongoing using various methodologies. For example, deficiencies in the growth hormone insulin-like growth factor cascade are associated with chronic pain at least in subgroup of patients with fibromyalgia [15]. A recent study using rectal biopsy samples has suggested that densities of rectal peptide YY and somatostatin cells are significantly altered in IBS patients [16].…”
Section: Editorialmentioning
confidence: 99%
“…Ancak yüksek maliyet ve olası yan etkiler (metabolik değişiklikler, karpal tünel sendromu ve anemi) kullanım konusunda endişe yaratmaktadır 85 .…”
Section: Büyüme Hormonuunclassified
“…The most recent clinical trial in this area was conducted under rigorous, randomized, doubleblinded, controlled conditions which showed that fibromyalgia patients, who were concomitantly receiving stable doses of amitriptyline, selective serotonin reuptake inhibitors and tramadol as part of their treatment regimen, and who also presented with the lowest levels of HGH and IGF-1, were most responsive clinically to supplemental HGH therapy [21]. However, a recent analysis by Blumenthal and Malemud [22] re-evaluated the data from that clinical trial [21] where the primary end-point measured in response to treatment with exogenous HGH was a reduction in the number of fibromyalgia tender points and concluded that, in fact, no statistically significant difference could be found between the HGH-treated and the placebo arm of the clinical trial in either primary or secondary end-points. Therefore, it can be concluded that the administration of HGH or supplemental HGR to alleviate the chronic pain of fibromyalgia remains controversial, to say the least.…”
Section: Journal Of Steroids and Hormonal Sciencementioning
confidence: 99%